Potentiometric and Chromatographic Study of Cu(II) and Al(III) Complexes of Quercetin - ÇIKLA YILMAZ, DENİZ (MARMARA UNIV, FAC PHARMACY, 2017)
In this study, the stability constants of the copper(II) and aluminium(III) complexes of quercetin were determined potentiometrically by using Calvin-Bjerrum and Irwing Rossotti methods. The protonation constants of quercetin were found: logK(1) = 11.15 +/- 0.118, logK(2) = 10.42 +/- 0.144, logK(3) = 9.44 +/- 0.162, logK(4) = 8.28 +/- 0.151. For copper complex formation constant was found by Irwing-Rossotti method: logK(1) = 19.92 +/- 0.367 and for aluminium complex complex: logK(1) = 23.02 +/- 0.459. From the results, the components of quercetin / metal complexes are given as 1/1 both copper(II) and aluminium(III). A reversed phase high pressure liquid chromatographic method was developed for the metal complexes which were prepared according to potentiometric results with the ratio quercetin / metal = 1/1. Mobile phase was 0.01 M HClO4/8.33 x 10(-5) M quercetin in Methanol (40/60), column was XTerra RP18, 5 mu m, 4.6 x 150 mm, detector was Diode Array Detector at lambda = 373 ve 421 nm (band width 4nm).
Keywords: Flavonoid-metal complexes; quercetin complexes; biologically active ligands; antioxidants; flavonoids; PERFORMANCE LIQUID-CHROMATOGRAPHY; METAL-COMPLEXES; ANTIOXIDANT ACTIVITY; FORMATION CURVES; FLAVONOIDS; STABILITY; THERAPY